Open IoT data platform for Uniandes campus (2022)
This document proposes a software architecture for an open data platform of IoT data for the Universidad de Los Andes, Colombia. The proposed open data platform is set to be developed as part of the digital transformation of the university and targets the need for a smart campus. This software architecture aims to integrate data collected from IoT devices across campus to make it available for download to students, researchers, and professors. Incorporating insights from a systematic literature review, key quality attributes were identified for the later proposal of a compli ant software architecture. Integration of core components of the architecture demonstrates the feasibility of the design for extract ing, transforming, and mapping heterogeneous data sources into a common data format for later use. Additionally, the proposed graphic user interface design is shown.